Особенности формирования импульсов в согласующих узлах магнитно-полупроводниковых генераторов - Волков, И.В.; Зозулев, В.И.; Шолох, Д.А.; Спирин, В.М. (Технічна електродинаміка, 2012)
The results of studies of formation pulses of micro- and nanosecond ranges of matching nodes magnetic semiconductor generators are analyzed. The dependences of the amplitude and duration of the current pulse in these nods from the time of its overlap with the previous current pulses is determined.